Henry [videorecording (DVD)] : portrait of a serial killer - McNaughton, John, 1950-; Rooker, Michael, 1955-; Arnold, Tracy; Towles, Tom, 1950-2015 (Dark Sky Films, 2005)
Based on true events, John McNaughton's film follows Henry's senseless killing sprees. Ex-convict Otis invites Henry to share his Chicago apartment and he becomes involved in Henry's killing sprees. Otis' sister comes to visit her brother, and she is fascinated with Henry and thinks his life resembles hers.